Stress Management in Sports: Based on Group Coping Theory and Dyadic Coping Theory - حبيب , بن صافي; سايح , زليخة (Journal of Sport Science Technology and Physical Activities, 2025)
This study aimed to shed light on the nature of the coping strategy developed by group members in response to common stressful situations. Given the multiple sources of stress and emotions within groups or teams in the sports context, two theoretical models were highlighted: the group coping theory and the dyadic coping theory. Their implications, dimensions, and functions in developing coping strategies were clarified. To combat psychological pressures and transform them from individual actions to collective ones, as they are related to expanding the scope of knowledge about the personal dimension of stress and sports adaptation processes